Investigating mixed biosolids and cardboard for methylene blue adsorption: Activation, adsorption modelling and thermodynamics - Shifa Zuhara (14150862) (2023)
Ongoing global population boom has led to the rise in waste and related research on increasing its economic value. In such an attempt, this study aims to activate gas-to-liquids (GTL) derived biosolids (BS) and cardboard (CB) and mixed samples (50:50) using potassium carbonate to produce three activated carbons (ACs): KBS, KCB and KM respectively. The characterization of the samples revealed surface areas of 156, 515, and 527 m2/g for KBS, KCB, and KM, respectively based on Brunauer–Emmett–Teller (BET) analysis, with increased porosity and metal content after activation evident from the Scanning Electron Microscopy-Energy Dispersive Spectroscopy (SEM-EDS) results, as well as the presence of magnetite in the KBS and KM samples apparent from the X-ray powder diffraction (XRD) results. Additionally, Fourier Transform Infrared Spectroscopy (FTIR) results indicate increased C–O–C stretches and O–H bonds after activation of the samples. The ACs were used for methylene blue (MB) removal process which is a rapid for all three samples, reaching equilibrium after 9 h, and optimal at neutral pH and maximum at the highest temperature, 40 °C. The MB adsorption capacity was highest for KM (191.07 mg/g), followed by the KCB and KBS samples. Isotherm modelling of the samples showed best fits for KBS, KCB and KM as Langmuir-Freundlich (LF), Langmuir and Toth models respectively. On the contrary, kinetic modelling using contact time study data for all samples exhibited best fits by the Diffusion-chemisorption (DC) model. Finally, the thermodynamic calculations of the mixed sample disclosed the adsorption process to be exothermic and spontaneous, with potential mechanisms being electrostatic attraction, ion exchange, π-π interactions, and hydrogen bonding. Multiple cycles of KM regeneration was also achieved with good adsorption capacities. Future work will explore other activation methods and examine the magnetic properties of KBS and KM for real water treatment. Other Information Published in: Environmental Research License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.envres.2023.115534